Judge's Advice in the Decisions of Marriage Dispensation Cases: Analysis Based on PERMA No. 5 of 2019 - Maharani, Tiara; Hidayat, Fitri; Suwardiyati, Rumi (Sakina: Journal of Family Studies, 2025)
The Qur'an and al-Sunnah as the main sources of Islamic law and guidelines for the lives of Muslims do not explain in detail and in depth the concept of husband's Nafkah to his wife. This requires the Mujtahids and their successors to perform Ijtihad in an effort to interpret the intentions of Shari'. One of the line of scholars who performed ijtihad so as to pour it into a work was Sheikh Zainuddin al-Malibari in his work Qurat al-'Ain which was further elaborated in more depth and detail by the Nusantara Syarh specialist Sheikh Nawawi al-Bantani in his work Nihayat al-Zein. Therefore, the purpose of this paper is to describe and explain the thoughts of Sheikh Nawawi on his in-depth elaboration of the Matn Qurrat al-'Ain. The approach used is Qualitative with the type of library research on the book of Nihayat al-Zain with the specification of text analysis. In order to get more comprehensive study results and to examine the relevance of Sheikh Nawawi's thoughts in the contemporary era, the Intertextual approach, the Reinterpretation approach and the Relevance approach are used. The result is the thought of Sheikh Nawawi on the concept of Nafkah, in some ways it is still relevant to be applied in the contemporary era and even requires an elitist life. But in some ways it is less relevant and even not applicable if confronted with the opinions of other figures.